The Concept and Value of the Teaching of Karma Yoga According to the Bhagavadgita Book - Ni Made Anggreni (Institut Hindu Dharma Negeri Denpasar, 2017)
Bhagawadgita is one of the Vedic supplements in which there are teachings of Karma Yoga, which contain the working concepts as a guide for Hindus in order to meet the physical and spiritual needs to achieve happiness. The teaching of Karma Yoga revolves around the way or way of achieving the perfection of life by carrying out the work as required by the swadharma by not binding itself to the outcome of the work itself. Working in non-self-bondage is to work with devotion and devotion to Bharman without expecting personal gain for the welfare and happiness of fellow human beings. In more modern interpretations, it may be shown as the obligatory acts performed without justifying the decision to explain one's actions. This teaching focuses on the action of work without being shackled by the work itself.